Multiwavelength Observations of the Blazar BL Lacertae: A New Fast TeV Gamma-Ray Flare - A. U. Abeysekara; W. Benbow; R. Bird; T. Brantseg; R. Brose; M. Buchovecky; J. H. Buckley; V. Bugaev; M. P. Connolly; W. Cui; M. K. Daniel; A. Falcone; et al. (IOP PUBLISHING LTD, 2022)
Combined with measurements made by very-long-baseline interferometry, the observations of fast TeV gamma-ray flares probe the structure and emission mechanism of blazar jets. However, only a handful of such flares have been detected to date, and only within the last few years have these flares been observed from lower-frequency-peaked BL. Lac objects and flat-spectrum radio quasars. We report on a fast TeV gamma-ray flare from the blazar BL. Lacertae observed by the Very Energetic Radiation Imaging Telescope Array System (VERITAS). with a rise time of similar to 2.3 hr and a decay time of similar to 36 min. The peak flux above 200 GeV is (4.2 +/- 0.6) x 10(-6) photon m(-2) s(-1) measured with a 4-minute-binned light curve, corresponding to similar to 180% of the flux that is observed from the Crab Nebula above the same energy threshold. Variability contemporaneous with the TeV gamma-ray flare was observed in GeV gamma-ray, X-ray, and optical flux, as well as in optical and radio polarization. Additionally, a possible moving emission feature with superluminal apparent velocity was identified in Very Long Baseline Array observations at 43 GHz, potentially passing the radio core of the jet around the time of the gamma-ray flare. We discuss the constraints on the size, Lorentz factor, and location of the emitting region of the flare, and the interpretations with several theoretical models that invoke relativistic plasma passing stationary shocks.